European red list of habitats - Part 2. Terrestrial and freshwater habitats - Janssen, J. A. M.; Rodwell, J. S.; Garcia Criado, M.; Gubbay, S.; Haynes, T.; Nieto, A.; Sanders, N.; Landucci, F.; Loidi, J.; Ssymank, A.; Tahvanainen, T.; Valderrabano, M.; et al. (European Commission, 2016)
The European Red List of Habitats provides an overview of the risk of collapse (degree of endangerment) of marine, terrestrial and freshwater habitats in the European Union (EU28) and adjacent regions (EU28+), based on a consistent set of criteria and categories and detailed data and expertise from involved countries (http://ec.europa.eu/environment/nature/knowledge/redlist_en.htm). Amongst terrestrial and freshwater habitats the highest percentage of threatened types (categories Critically Endangered, Endangered, Vulnerable) was found amongst mires and bogs (85% in the EU28, 54% in the EU28+), followed by grasslands (53%, 49%), freshwater habitats (46%, 38%) and coastal habitats (45%, 43%). Relatively low percentages of heathland and scrub, forests, and sparsely vegetated habitats were assessed to be threatened. Overall the amount of threatened habitats was higher in the EU28 (36%) than in the wider range of the EU28+ (31%). The European Red List of Habitats provides extensive additional information on habitat classification and definition, pressures and threats, conservation and restorability of habitats, distribution, status and trends in individual countries, and sub-habitats that may possibly be threatened. The information provided can inform and support European nature and biodiversity policy in a variety of ways, particularly in relation to the EU2020 Biodiversity Strategy targets. Further applications include the revitalisation of the EUNIS habitat classification, synergies with the Mapping and Assessment of Ecosystems and their Services initiative, and the improvement of Red List methodologies
Keywords: uhanalaisuus; uhanalaiset lajit; biodiversiteetti; luontotyypit